Unusual fungal infection of conidiobolomycosis presenting as nasal tumor – A - Agale, Shubhangi; Rathi, Vanita; Tandale, Monica (Indian Journal of Case Reports, 2024)
Conidiobolomycosis is an unusual chronic subcutaneous fungal infection belonging to the order Entomophthorales of zygomycetes. It commonly affects the upper respiratory tract, mucous membranes of the upper lip, and subcutaneous tissues. Clinically, it presents as painless woody swelling commonly affecting the rhinofacial region causing extensive facial deformity. Due to its rarity and the lack of awareness, the diagnosis can be challenging. The definitive diagnosis of rhinofacial conidiobolomycosis is based on histopathological examination of skin lesions. The awareness of this entity is important for early diagnosis and patient management which helps in reducing morbidity associated with disease. We report a rare histopathologically diagnosed case of conidiobolomycosis in a 17-year-old male which was clinically considered a vascular tumor and radiologically diagnosed as hemangioma.